2004
DOI: 10.1111/j.1442-2042.2003.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Filarial chyluria: Long‐term experience of a university hospital in India

Abstract: Background : Filariasis is an endemic problem in various Indian states. We evaluated the results of long-term follow up (10-20 years) of patients with filarial chyluria. Methods : We conducted a retrospective analysis of 160 patients treated for filarial chyluria who presented to the Banaras Hindu University Hospital from 1982 to 1992. Eighty-four patients (52.5%) were treated using diethylcarbamazine (DEC) and a fat restricted diet and 76 patients (47.5%) underwent surgery. To examine the long-term effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…In the year 2000, WHO started a worldwide campaign to eliminate filariasis. India contributes about 40% of total global burden and accounts for nearly 50%of the people at risk of filarial infection and the province of Uttar Pradesh has the highest prevalence, with 7 million affected people [2][3][4]. Chyluria occurs in up to 10% of patients with filariasis [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2000, WHO started a worldwide campaign to eliminate filariasis. India contributes about 40% of total global burden and accounts for nearly 50%of the people at risk of filarial infection and the province of Uttar Pradesh has the highest prevalence, with 7 million affected people [2][3][4]. Chyluria occurs in up to 10% of patients with filariasis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fat intake, pregnancy and exercise are considered to be aggravating factors of chyluria, and these conditions should be avoided, especially in patients with recurrent or prolonged chyluria (16). In the present case, moderate to severe fatty liver was confirmed, which may have directly induced the patient's chyluria.…”
Section: A Bmentioning
confidence: 70%
“…The symptoms of lymphatic obstruction generally appear one or two years after infection. It has been reported that chyluria has occurred in two (1.7%) of 119 filarial patients (13), two (2.5%) of 80 filarial patients (14) and up to 10% of filarial patients (15,16). Therefore, the complication of chyluria is a relatively rare condition in patients with filariasis.…”
Section: A B C Dmentioning
confidence: 99%
See 2 more Smart Citations